The Role of Digital Leadership in Improving the Performance Productivity of State Civil Apparatus in the Era of Digital Transformation - Murad Lahadji; Wahyu Aji Purnama (Jurnal Multidisiplin West Science, 2026)
Digital transformation in the public sector requires the State Civil Apparatus (ASN) to not only be proficient in technology but also operate in a bureaucratic ecosystem that is led in an adaptive, innovative, and data-driven manner. This study aims to explore the role of digital leadership in increasing the productivity of ASN performance in the era of digital transformation. This study used a quantitative approach with an explanatory survey design. Data were collected through a Likert 1–5 scale questionnaire that included five indicators of digital leadership and five indicators of ASN performance productivity at the Banggai Regency Investment and One-Stop Integrated Services Office (DPMPTSP). The research sample consisted of 30 ASN. The analysis was carried out using descriptive statistics, the validity test of item-total correlation, the reliability of Cronbach's Alpha, the Pearson and Spearman correlation, and simple linear regression. The results showed that digital leadership was in the very high category with an average score of 4.85, while the productivity of ASN performance was also in the very high category with an average score of 4.90. The instrument showed good reliability, with Cronbach's alpha for the digital leadership variable of 0.889 and performance productivity of 0.968. The relationship between digital leadership and ASN performance productivity was positive and significant according to both Pearson (r = 0.398; p = 0.030) and Spearman (rho = 0.483; p = 0.007). The regression model yielded a coefficient of B = 0.362 with R² = 0.158, suggesting that digital leadership explains about 15.8% of the variation in performance productivity. However, these results need to be interpreted with caution due to the limited sample size and tendency of the ceiling effect. This study emphasizes the importance of digital leadership as a driver of ASN productivity through technology-based direction, digital work adaptation, collaboration, and the formation of a culture of innovation.